2019
DOI: 10.3390/polym11091504
|View full text |Cite
|
Sign up to set email alerts
|

Application of Xanthan Gum as a Pre-Treatment and Sharpness Evaluation for Inkjet Printing on Polyester

Abstract: Inkjet printing on polyester fabric displays versatile environmental advantages. One of the significant benefits of inkjet printing is a dramatic enhancement of the printing quality. In this study, xanthan gum—a bio-based thickening agent accompanied by several salts—was adopted for the pretreatment of polyester fabric aiming at improving the sharpness and color depth of inkjet printed patterns. The influences of four metal salts (NaCl, KCl, CaCl2 and MgCl2) on inkjet printing performance were studied. More im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Cao, H. et al 53 reported that the pre-treatment of polyester fabric using xanthan gum and salt can enhance the color penetration and printing clarity of inkjet printing, and the divalent salt can give higher K/S values and printing clarity. The most preferable pretreatment condition was (0.3% xanthan gum paste and 0.1 mol/L calcium chloride).…”
Section: Application Of Thickening Agent On Textile Printingmentioning
confidence: 99%
“…Cao, H. et al 53 reported that the pre-treatment of polyester fabric using xanthan gum and salt can enhance the color penetration and printing clarity of inkjet printing, and the divalent salt can give higher K/S values and printing clarity. The most preferable pretreatment condition was (0.3% xanthan gum paste and 0.1 mol/L calcium chloride).…”
Section: Application Of Thickening Agent On Textile Printingmentioning
confidence: 99%
“…Despite a large number of publications on biodegradable and environmentally friendly marker inks reported in the literature in recent years [ 7 , 20 , 21 , 22 ], most studies were carried out in the one-factor-a-time (OFAT) approach. For greater efficiency, the application of statistical analysis and regression coefficient (mathematical model) are necessary for better prediction on the optimum composition of marker ink with high color lightness and low viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…17 prepared cationic copolymer nanosphere dispersion by soap-free emulsion polymerization, which attached to the fabric, significantly enhancing the color performance of inkjet printed fabrics. Other pretreatments, including xanthan gum, 2 cationic primer, 18 and low free water content inks, 1921 all improve the sharpness of the printed pattern to a certain degree. However, these methods entail a long treatment process and high energy consumption, water use, and process time (Scheme 1).…”
mentioning
confidence: 99%
“…Digital inkjet printing also needs less water, produces less pollution, and is less labor-intensive than traditional printing. [1][2][3] Digital inkjet printing technology generally includes transfer printing and direct printing. Transfer printing is mainly applied to materials such as high-temperature-resistant polyester or nylon.…”
mentioning
confidence: 99%
See 1 more Smart Citation